Cardiac sarcoidosis – an expert review for the chest physician. (3rd June 2019) - Ho, Jamie S. Y.; Chilvers, Edwin R.; Thillai, Muhunthan
ABSTRACT: Introduction : Sarcoidosis is a multisystem granulomatous disease predominantly affecting the lungs, with increased risk of cardiovascular disease, pulmonary hypertension and cardiac sarcoidosis (CS), the latter due to direct granuloma infiltration. Sarcoidosis is often managed by chest physicians who need to understand the diagnostic pathways and initial management plans for patients with cardiac involvement. Areas covered : The most serious consequence of CS is sudden cardiac death due to ventricular tachyarrhythmias or complete atrioventricular block. Additional complications include atrial arrhythmias and congestive cardiac failure. There are no internationally accepted screening pathways, but a combination of history, clinical examination and ECG detects up to 85% of cases. Newer modalities including signal-averaged ECG and speckle-tracking echocardiography increase identification of patients who require a definitive diagnosis. Early immunosuppression reduces the risk of conduction abnormalities and incidence of supraventricular arrhythmias. Management of ventricular arrhythmias requires antiarrhythmic medications followed by possible catheter ablation and device (ICD) implantation. Expert commentary : Prospective trials are underway to identify the optimum methods for screening, which will guide future international statements on indications for and methods of screening in CS.